ON THE ARRIVAL TRAFFIC FLOW ORGANIZATION - N. A. Assorov (Научный вестник МГТУ ГА, 2017)
This article is about air traffic flow organization, ICAO regulations describe the organizing of traffic flow as one of the purposes of air traffic control, but they don’t state exactly at what point the flow has to be organized and metered. The flight phase, where air traffic controller interferes with his instructions in order to begin organizing of all aircraft landing at a certain airport depends on the actual traffic volume per hour, airspace capacity and design.The example of air traffic situation in Moscow Domodedovo airport is described in the article, with runway 32 right in use, no significant weather, real usage of STARs, considering all the ICAO and Russian Federation regulations regarding speed control with the restrictions mentioned in AIP of Moscow Domodedovo. The purpose of the experiment is to prove the need of metering the air traffic flow on the entry points in Moscow TMA, because in case of unorganized air traffic flow approach controllers will have additional unnecessary workload.The conducted calculations show, that only 3 aircraft entering TMA on the same distance from initial approach point can be handled using only speed control and existing standard arrival procedures, in all other cases vectoring or holding areas should be used.In order to avoid such situations and increase the number of the aircraft that can be handled by the approach controller with less instructions, all the traffic arriving on the TMA entry point has to be metered by area control centre, because the air traffic control unit has much more space and time for long term speed control modifications, e.g. ±0,02 Mach. In conclusion a simple rule comes to mind – the bigger inbound traffic is, the earlier one has to organize it, in order to do it speed control, radar vectors, miles-in-trail can be used. Also new equipment and technology can help air traffic controller with this task, e.g. AMAN (arrival manager), in addition to this, the experience of London Heathrow airport, which increases the AMAN horizon from 150 nm to 600 nm, has to be studied by all concerned air traffic providers.